Social Support, Personality Traits, Social Innovation Mempengaruhi Intensi Kewirausahaan Sosial: Entrepreneurial Attitude Sebagai Mediasi - Dion Nathanael; Kartika Nuringsih (Jurnal Manajerial Dan Kewirausahaan, 2020)
The purpose of this research is to examine whether social support, personality traits, social innovation orientation can affect social entrepreneurial intention in Tarumanagara University: entrepreneurial attitude as a mediating variable. The research method used in this study is the coefficient of determination method (R2) with the result 0,596, predictive relevance (Q2), effect size (F2), path coefficient, and hypothesis testing. The populations of this research are all Tarumanagara University students who take entrepreneurial concentration or have taken courses in social entrepreneurship. Data processing techniques using structural equation modeling by using  SmartPLS 3.0 program. The results of this study are social support, personality traits, social innovation orientation, and entrepreneurial attitude (mediating variables) significantly to predict social entrepreneurial intention. Penelitian ini bertujuan untuk mengetahui social support, personality traits, social innovation orientation mempengaruhi intensi kewirausahaan sosial di Universitas Tarumanagara: entrepreneurial attitude sebagai mediasi. Metode penelitian yang digunakan dalam penelitian ini yaitu koefisien determinasi (R 2 ) dengan hasil sebesar 0,596, predictive relevance (Q2 ), effect size (F2 ), path coefficient, dan pengujian hipotesis. Populasi dari penelitian ini adalah seluruh mahasiswa Universitas Tarumanagara yang mengambil konsentarasi kewirausahaan atau sudah mengambil mata kuliah kewirausahaan sosial. Teknik pengolahan data menggunakan pemodelan persamaan struktural dengan menggunakan program SmartPLS 3.0. Hasil dari penelitian ini adalah social support, personality traits, social innovation orientation, dan entrepreneurial attitude (variable mediasi) signifikan mempengaruhi intensi kewirausahaan sosial.